Friday

July 25, 2014

July 25, 2014

Posted by **Bob** on Thursday, April 25, 2013 at 11:56pm.

- Solve the following polynomial equati -
**Steve**, Friday, April 26, 2013 at 5:01amWell, since the product of the roots is (a+1)(a+3) my first guess would be

(x-(a+3))(x-(a+1))

= x^2 - (a+1)x - (a+3)x + (a+1)(a+3)

= x^2 - (2a+4)x + (a+1)(a+3)

= x^2 - 2(a+2)x + (a+1)(a+3)

ta-daaa.

**Related Questions**

Finding polynomial from zeros - How to find the polynomial degree 2 and zeros ...

algebra - solve the polynomial y=2x^2-4x+1 I am sure neither your text nor your ...

polynomials - i also have theses to solve Factor the polynomial x2 + 5x + 6 ...

Math - Factor the polynomial P(x)=x^3-2x^2-13x-10. Then solve the equation P(x)=...

calculus-can someone please help me with this ques - Find all zeros of the ...

Algebra 2 - Find the distance between the points (12, 8) and (4, 2). 100 units ...

Algebra -polynomial - Solve the polynomial 40x^2+2x-65 Notice that for x = 1 the...

Algebra - If 3 is a zero of the polynomial f(x), then which of the following is ...

math - Solve the following polynomial inequalities. 4x - 5 ≤ 2(x - 7)

math - Solve the following polynomial inequalities. a) 4x - 5 ≤ 2(x - 7)